2008
DOI: 10.5558/tfc84037-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timing of glyphosate application on jack pine, black spruce, and white spruce plantations in northern Manitoba

Abstract: Deferring conifer release treatments is sometimes necessary, but its effects on crop tree performance are not well understood. We investigated the effects of deferring glyphosate applications on jack pine (Pinus banksiana Lamb.), black spruce (Picea mariana [Mill.] BSP), and white spruce (Picea glauca [Moench.] Voss.) plantations established on a dry site with moderate competition and a moist site with heavier competition in The Pas, northern Manitoba. At each site, experimental treatments included no herbicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
(24 reference statements)
1
11
1
Order By: Relevance
“…But, after eight growing seasons, REL5 seedlings had yet to catch up with REL3 seedlings in terms of absolute dimensions, even though the height and diameter differences could be considered of limited silvicultural impact. These results differ slightly from those reported by Fu et al [46], who compared tenth-year effects of delayed aerial glyphosate applications from year 1 to 5: at the end of their experiment, all treatments had produced similar-sized saplings. As illustrated in Figure 7, REL3 provided the crop-trees with ∼85% full sunlight during at least two seasons (4 and 5) during which REL5 seedlings continued to receive <60%PAR.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…But, after eight growing seasons, REL5 seedlings had yet to catch up with REL3 seedlings in terms of absolute dimensions, even though the height and diameter differences could be considered of limited silvicultural impact. These results differ slightly from those reported by Fu et al [46], who compared tenth-year effects of delayed aerial glyphosate applications from year 1 to 5: at the end of their experiment, all treatments had produced similar-sized saplings. As illustrated in Figure 7, REL3 provided the crop-trees with ∼85% full sunlight during at least two seasons (4 and 5) during which REL5 seedlings continued to receive <60%PAR.…”
Section: Discussioncontrasting
confidence: 57%
“…Nevertheless, the height/diameter ratios remained well below critical levels for plantation stability [3], even in control plots. Concomitant with the general pattern observed elsewhere (e.g., [46,47]), resource competition by noncrop species had limited influence on seedling survival in the short term. However, competition pressure in control plots is expected to induce mortality in the longer term, compared to treated plots [48], which, in turn, will have a significant impact on crop-tree production [49].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Results from studies in eastern Canada indicate that conifers generally show greater growth responses to early (e.g., site preparation before tree planting) treatments than to delayed treatments [14,15]. However, a study in Manitoba, Canada, showed no effects of age of treatment (between 1 and 5 years after planting) on growth of white spruce, black spruce, or jack pine resulting from a single aerial application [16]. In this experiment, the response was attributed to the replacement of woody vegetation by herbs and grasses following a single herbicide treatment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Vigorously growing competing vegetation can negatively affect site conditions and factors such as water availability (Nilsson et al 1996;Nilsson & Örlander 1999), nutrients (Nilsson et al 1996;Jobidon 2000), light (Nilsson et al 1996;Jobidon 2000), and temperature (Jobidon et al 2003). It is well known that high stocking densities of hardwoods can critically hinder the growth of the more desirable conifer trees (Walfridsson 1976;Folkesson & Bärring 1982;Andersson 1993;Jobidon 2000;Fu et al 2008;Bataineh et al 2013). Fierce competition from competing vegetation can eventually cause crop-tree mortality (Jobidon 2000).…”
Section: Juvenile Stand Management and The Techniques Used For Itmentioning
confidence: 99%